Surgical Targeting of Recurrent Thyroid Cancer Using a Novel Mixture of 99m-Technetium Macroaggregated Albumin and Indocyanine Green. (December 2014) - Jung, Yuh-S.; Kim, Seok-ki; Park, Insoo; Ryu, Junsun; Kim, Seok Won; Lee, Chang Yoon; Lee, Jia
Background . Precise targeting has played a pivotal role in the success of surgery for recurrent differentiated thyroid cancers (DTCs). To improve on current targeting methods, we developed a novel technique using 99m Tc-macroaggregated human serum albumin and indocyanine green (TIGMA), with which surgeons effectively target lesions in real time by radiofluorescence dual guidance. Methods . Seven patients with 10 recurrent DTC lesions were retrospectively enrolled in the study. Prior to the operation, we injected TIGMA into the target lesion under the guidance of ultrasonography. Resection was concurrently monitored using a gamma probe and a specially designed near infrared fluorescence camera. Outcomes were evaluated using imaging, surgical, and pathological records. Results . In all enrolled cases, both injection of TIGMA and radiofluorescence dual guidance were well tolerated and easy to implement. The technical success rates were 100%, confirmed by final pathological examination, postoperative ultrasonography, and I-131 scan clearance. Complications such as temporary postoperative neck pain (n = 2) were minimal. Conclusions . TIGMA using radiofluorescence dual guidance facilitated the precise targeting of recurrent lesions. The entire procedure was feasible, safe, and successful. This method would help enhance surgical outcomes for recurrent DTCs.